Developing Transversal Competencies through technology: Integrating Google Workspace for Education in the language teaching and learning processes - Kakoulli-Constantinou, Elis (My University, 2026)
Workshop delivered at the CyTEA Annual Conference: Development of Transversal Competencies: Current Educational Realities.